2019
DOI: 10.7547/17-200
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Angular Osteologic and Radiographic Measurements of the Human Talus and Calcaneus

Abstract: Background: Radiographic imaging of the foot is commonly performed when medical evaluation is indicated. Angular measurements between bones may be assessed as part of the examination for trauma and foot biomechanics. However, angular relationships between surfaces of the physical bone as they compare with the bone's radiographic image has had limited investigation. Methods: For this study, 54 human feet from amputated limbs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…It is also clear that the ankle angle at all phases of performance was less than normal after the injury, while it returned to its normal position (Agoada & Kramer, 2019;Tomaro & Butterffield, 1995) And the ankle angle has increased significantly after recovery, as the Subtalar Joint is one of the Plane joint (Marieb & Jackson, 2018;Netter, 1951;Rockar, 1995) It is one of the highly affected joints when injured, and the injury causes it to reduce the angle of the foot, the inability to straighten the metatarsal at its natural angle . (Badalahu et al, 2020;Rockar, 1995) The results of the study indicate that the joint angle has returned to its normal position, which indicates the elimination of the effect of fibrosis resulting from an unhealed fracture that was not properly treated.…”
Section: Discussionmentioning
confidence: 98%
“…It is also clear that the ankle angle at all phases of performance was less than normal after the injury, while it returned to its normal position (Agoada & Kramer, 2019;Tomaro & Butterffield, 1995) And the ankle angle has increased significantly after recovery, as the Subtalar Joint is one of the Plane joint (Marieb & Jackson, 2018;Netter, 1951;Rockar, 1995) It is one of the highly affected joints when injured, and the injury causes it to reduce the angle of the foot, the inability to straighten the metatarsal at its natural angle . (Badalahu et al, 2020;Rockar, 1995) The results of the study indicate that the joint angle has returned to its normal position, which indicates the elimination of the effect of fibrosis resulting from an unhealed fracture that was not properly treated.…”
Section: Discussionmentioning
confidence: 98%
“…Subgroup analysis revealed that the Asian population had a higher DA (20.873°, 95%CI, 14.216-27.530) than the Non-Asian population (16.672°, 95%CI, 12.414-20.931); however, this difference was not statistically significant. The coefficient of variance for this parameter was determined to be high for three studies [ 16 , 17 , 20 ], and low for others. Two studies evaluated the DA in the pediatric population [ 20 , 25 ].…”
Section: Reviewmentioning
confidence: 99%
“… Inclination angle measurement methods: (a) the method described by Bonnel et al [ 17 ]; (b) the measurement method described by Agoada et al [ 16 ]; (c) the method described by He et al [ 15 ] and Mahato et al [ 21 ]; (d) the method described by Motagi et al [ 23 ]. All meta-analysis values are in degrees.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations